FROM SEMANTICS TO PRAGMATICS: THE APPLICATION AND DIDACTIC USE OF PROVERBS IN ENGLISH AND UZBEK LANGUAGE TEACHING - Axmedov , Ikboljon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
Proverbs are seen as a special mix of word meanings, practical uses, and culture codes. They are considered powerful but little-used tools in foreign language teaching. Their teaching value in English and Uzbek classes is examined in this study. The change from understanding words to using them in talk is followed. A qualitative comparison method is employed. The role of proverbs in building students’ talk skills, culture awareness, and right speaking is explained. A collection of teaching-important English and Uzbek proverbs was studied for meanings, uses, and teaching value. It was found that proverbs are usually taught as word items first. Their talk functions-like advice, warnings, judging, persuading—are not used enough in class. Proverb teaching is argued to clearly improve talk skills and culture knowledge. Practical ideas for class design, materials, and teacher training in English and Uzbek programs are given.